School Library as a Mediator of Reader Education in a Secondary School between 2019 and 2022 (London Journal of Research In Humanities and Social Sciences, 2024)
This scientific article is the result of two internship experiences in literature, the first of which took place between november and december 2019, during the observation internship in literature and the second, between may and june 2022, during the regency internship in literature. These were part of the undergraduate programme in Letters portuguese language at the University for the International Integration of Afro-Brazilian Lusophony (UNILAB-CE), which took place at the Camilo Brasiliense EEM High School located in the district of Antônio Diogo, Brazil. However, this research is limited to the data found in the school library. In this way, the scientific investigation aims to reflect on teh processo of literary mediation presente in the base texts of this research and to analyse, describe and compare how the literacy actions and the functioning of the School Library of the EEM Camilo Brasiliense School occurred between the firs internship carried out at the end of 2019, and the other, in a more recente time, in the first semestre of 2022. The study was based on theorists of literary literacy, such as Rosa (2022), Rocca(2012), Bezerra et al (2022), Alencar (2020), Nikel (2022), Campello (2010), Mesquita (2019), and Fiorovante (2018). The methodology applied was a comparative case study between two periods on the work of literary mediation by the library, and direct observation was carried out, the school’s collection and documents were consulted, and interviews were conducted with a semi-structured questionnaire for the librrian teachers and the teacher of Portuguese language and literature. The results show that a training process has begun for teachers to attend to the library in 2022, organising the categories of the literary collection, which facilitates acces, improving the structure of the physical space, engaging the library with education through the elective subjects offered, and in addition, the 2022 readership, in a post-pandemic context to, has shown a greater interest in Reading literary Works, compared to the readership at the end of 2019, and in addition to best-sellers reads books of Brazilian Literature, and on the recommendation of the teacher librarians. In addition, there are summarised books used for the Reading circle, although this practice was still in the process of being consolidated at the school.
Keywords: Auraco Tamed; Lope; indigenous body; Caupolic; hermeneutics.; textual theory; reader reception; aesthetic of reception; psychoanalytic theory; Alphonse Daudet; literary interpretation; adolescent readers; comprehension strategies; ethical appraisal; contemporary literary discourse.; Scientism; Modernity; Ethics; Cognitive Computing; Artificial Intelligence; COVID19; hunhu/ubuntu; vital force; social media marketing strategy and moral tool; School library; Reader education; Literary literacy.